Permutation group SN and large Nc excited baryons - Pirjol, Dan (2008)
We study the excited baryon states for an arbitrary number of colors Nc from the perspective of the permutation group SN of N objects. Classifying the transformation properties of states and quark-quark interaction operators under SN allows a general analysis of the spin-flavor structure of the mass operator of these states, in terms of a few unknown constants parametrizing the unknown spatial structure. We explain how to perform the matching calculation of a general two-body quark-quark interaction onto the operators of the 1/Nc expansion. The inclusion of core and excited quark operators is shown to be necessary. Considering the case of the negative parity L=1 states transforming in the MS of SN, we discuss the matching of the one-gluon and the Goldstone-boson exchange interactions. © 2008 The American Physical Society.